Turkish Foreign Policy and Public Opinion in the AKP Era. Issue 2 (3rd July 2012) - Kennedy, Ryan; Dickenson, Matt
<x xml:space="preserve">Abstract</x> Since the election of the Justice and Development Party (AKP) in 2002, Turkey has become the subject of increased attention from the US foreign policy community. Schools of thought range from those who argue that Turkey is "turning away from the West" to those who suggest that Turkey is pursuing a more autonomous foreign policy. One of the few things on which these schools of thought agree is that, if they are correct, we should be able to find these patterns in public opinion. Analyzing data from the Pew Global Attitudes Project, we find some differences in attitudes based on political party affiliation, income and education, but the results generally refute the argument that Turks see a fundamental choice between East and West in their foreign policy or that supporters of the AKP have fundamentally different international outlooks. Taken together, these results have important implications for US policymakers.